Development and validation of antisnake venom knowledge assessment tool (AKAT) for healthcare practitioners. (December 2020) - Bala, Auwal A.; Jatau, Abubakar I.; Yunusa, Ismaeel; Mohammed, Mustapha; Mohammed, Al-Kassim H.; Isa, Abubakar M.; Sadiq, Wada A.; Gulma, Kabiru A.; Bello, Inuwa; Malami, Sani; Michael, Godpower C.; Chedi, Basheer A.Z.
Abstract: Antisnake venom (ASV) is the only specific and standard treatment for snakebite envenoming worldwide. The knowledge of antivenom dosage, mode of administration, availability, and logistics is essential to the healthcare practitioners (HCPs) in the management of snakebites. It is vital for the HCPs involved in the handling of ASVs to have its basic knowledge. The ASV contains proteins and can, therefore, easily get denatured if not handled appropriately, leading to poor therapeutic outcome. It is also essential for clinicians to be aware of the tendency of ASV to cause a severe life-threatening hypersensitivity reaction. There is currently no validated tool for assessing the knowledge of ASV among HCPs. Therefore, we developed and validated a tool for evaluating the HCPs knowledge of ASV. The items included in the tool were first generated from a comprehensive literature review. Face validity were conducted by presenting the drafted tool to ten experts on the subject matter. A validation study was conducted among doctors, pharmacists, nurses, pharmacy technicians, and the general public. The objectives of the study were to test the tool for content validity using the content validity index (CVI), construct validity using contrast group approach, difficulty index, readability, and reliability test using the test-retest method. We developed and validated a final tool containing thirty-three items. The tool was valid for face validity and had a scale-level (average) content validity (S-CVI/Ave) of 0.91. The ASV knowledge of pharmacists was higher than that of doctors, pharmacy technicians, nurses, and the general public ( p  < 0.001), thus, valid for construct validity. The readability of the tool using the Simple Measure of Gobbledygook (SMOG) was determined to be grade level 7. The test-retest analysis showed no significant difference between the mean knowledge scores measured at four weeks interval ( p  = 0.916), implying excellent reliability. The AKAT has demonstrated good psychometrical properties that would enable its application among a wide range of healthcare practitioners. Highlights: A tool for assessing knowledge of anti-snake venom was developed and validated. Psychometrics approach was used in validating the knowledge assessment tool. The tool is reliable with a Simple Measure of Gobbledygook grade level 7. The tool can measure anti-snake venom knowledge among healthcare practitioners.